EFFECT OF DIFFERENT ECBOLIC THERAPY ON BLOOD METABOLIC PROFILE AND PROTEINOGRAM IN DYSTOCIA AFFECTED DANGI COWS - BHOI, D B; KHASATIYA, C T; DESAI, V K (The Indian Journal of Animal Reproduction, 2022)
The study was conducted on dystocia affected eighteen Dangi cows to investigate effect of different ecbolictherapies at calving on postpartum blood metabolic profile and proteinogram. Group-I (T1) and Group-II (T2) cowswere injected intramuscularly with methyl-ergometrine (5mg) and dinoprost tromethamine (25 mg), respectively, immediatelyafter parturition. Group-III (T3) cows received herbal ecbolic boli Exapar @ 2-4 boli, bid, PO for first 10 dayspostpartum. The mean plasma glucose levels were found significantly higher (P
Keywords: Dangi cow; Dystocia; Ecbolic; Metabolic profile; Postpartum; Protein